METHODOLOGY OF STUDYING OF A LITERARY WORK WITH THE HELP OF IMAGES OF NATURAL ELEMENTS DURING THE LESSONS OF UKRAINIAN LITERATURE IN 10-11 GRADES - Орищенко, Инна (SWorldJournal, 2020)
Abstract. Genre features of the work should always be studied during lessons of Ukrainian literature, however, as practice shows, they are considered in isolation from the content of the literary text. The article offers methodological approaches and str